2014
DOI: 10.1103/physrevb.90.245119
|View full text |Cite
|
Sign up to set email alerts
|

Exotic magnetic orderings in the kagome Kondo-lattice model

Abstract: We consider the Kondo-lattice model on the kagome lattice and study its weak-coupling instabilities at band filling fractions for which the Fermi surface has singularities. These singularites include Dirac points, quadratic Fermi points in contact with a flat band, and Van Hove saddle points. By combining a controlled analytical approach with large-scale numerical simulations, we demonstrate that the weak-coupling instabilities of the Kondo-lattice model lead to exotic magnetic orderings. In particular, some o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 60 publications
3
63
0
Order By: Relevance
“…The kernel polynomial method (KPM) can provide stochastic estimates of the electronic free energy [45]. The gradient transformation of the KPM energy estimation procedure yields density matrix elements, as required by Gutzwiller, with computational cost that scales linearly with system size for both insulating and metallic systems [46,47]. Another future direction is generalizing the extended Lagrangian (XL) formalism [48,49] to the GQMD self-consistency equations.…”
mentioning
confidence: 99%
“…The kernel polynomial method (KPM) can provide stochastic estimates of the electronic free energy [45]. The gradient transformation of the KPM energy estimation procedure yields density matrix elements, as required by Gutzwiller, with computational cost that scales linearly with system size for both insulating and metallic systems [46,47]. Another future direction is generalizing the extended Lagrangian (XL) formalism [48,49] to the GQMD self-consistency equations.…”
mentioning
confidence: 99%
“…These two triangular and honeycomb triple-M spin density wave states are examples of noncoplanar spin order. In fact, these spin density waves, which we have derived from symmetry principles here, are nothing but the chiral spin density waves found both in itinerant classical magnets and mean-field Hubbard model calculations on the triangular [26,[41][42][43], honeycomb [27,29,44], and kagome lattices [30,35,36]. The chiral spin density wave was also found in a honeycomb Hubbard model study using advanced quantum many-body techniques [18,19,23].…”
Section: S-wave Triplet States: Spin Density Wavesmentioning
confidence: 76%
“…They are scalar orders in the sense that they can be viewed as total angular momentum J = 0 terms. The first originates from the set of charge density or s waves and corresponds to a full spin-rotation symmetry broken spin density wave state, the so-called chiral spin density wave [26,27,35,36], associated with a gapped mean-field spectrum. The mean-field ground state is a Chern insulator.…”
Section: Overview and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the abundance of these non-coplanar incommensurate orders and the lack of attention given to such orders in previous studies 12,13,33 of the Kondo Lattice Model, we set about exploring their origin in further detail. Using LuttingerTisza and Fermi surface geometry arguments in Section III, we showed that the ordering wave-vectors of the spin configurations were the nesting wave-vectors of the Fermi surface (Fig.3).…”
Section: )(D)(also See Appendices B and D)mentioning
confidence: 99%